In Vitro Antidiabetic and Antioxidant Activities of Aqueous Extract from the Leaf and Fruit of Psidium guajava L. - Adelina Simamora; Lusia Paramita; Nur Azreen; Adit Widodo Santoso; Kris Herawan Timotius (Indonesian Biomedical Journal, 2018)
BACKGROUND: The leaf and fruit of Psidium guajava L. are potential for neutraceutical beverage especially for antidiabetic drink. The aims of this study were to determine the antidiabetic activity of aqueous extract of leaf (LE) and fruit (FE) from P. guajava.